9p21.3 risk locus is associated with first-ever myocardial infarction in an Austrian cohort. Issue 8 (August 2016) - Haslacher, Helmuth; Perkmann, Thomas; Ratzinger, Franz; Grimm, Gabriele; Exner, Markus; Keller, Alexandra; Schmetterer, Klaus; Priemer, Clemens; Endler, Georg; Wagner, Oswald; Schillinger, Martin
Abstract : Aims: Atherosclerosis often presents as a complex systemic disease that is strongly influenced by lifestyle factors, but also by the genetic background. The sequence variant rs1333049 affects the expression of ANRIL, a noncoding RNA transcript playing a key role in the regulation of inflammatory processes. We thus aimed to replicate the predictive value of genetic information on this variant regarding the development of cardiovascular events in an Austrian high-risk cohort. Methods: Nine hundred and eighty-eight patients from an angiologic outpatient ward at a large University hospital were genotyped by means of the 5'-nuclease assay. Relative risk ratios were assessed for carriers of different alleles. Statistical independence of genetic information was evaluated in multivariable analysis including known risk markers. Results: In patients carrying the [G]-allele, metabolic parameters (serum low-density lipoprotein, total cholesterol) significantly decreased during the initial 6 months of the observation period ( P  < 0.01). Likewise, homozygous [C]-allele carriers were at a higher risk of suffering myocardial infarction (relative risk = 2.681, 95% confidence interval 1.418–5.070). In contrast, we found no interaction between rs1333049 genotype and progression of carotid atherosclerosis or stroke. Conclusions: These results are in line with the previous findings, suggesting that genetic information on the rs1333049 variant might be a useful predictor of adverse cardiac events. Thus, we could successfully replicate the predictive value of the 9p21 risk allele in an Austrian cohort.